2018
DOI: 10.1101/264804
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morphometric analysis of spread platelets identifies integrin αIIbβ3-specific contractile phenotype

Abstract: Haemostatic platelet function is intimately linked to cellular mechanics and cytoskeletal morphology. How cytoskeletal reorganizations give rise to a highly contractile phenotype that is necessary for clot contraction remains poorly understood. To elucidate this process in vitro, we developed a morphometric screen to quantify the spatial organization of actin fibres and vinculin adhesion sites in single spread platelets. Platelets from healthy donors predominantly adopted a bipolar morphology on fibrinogen and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 61 publications
3
7
0
Order By: Relevance
“…Adhesion signaling of either α6β1 on laminin, α2β1 on Col4, or αIIbβ3 on Fn or fibrin is sufficient to drive αIIbβ3 to assemble Fn fibrils (Figures 1,2,6), in analogy to the pre-activation of α5β1 integrins by αvβ3 in fibroblasts Bharadwaj et al 2017), the initiation of α5β1-containing sliding fibrillar adhesions by α3β1 or α2β1 integrins on Matrigel (Lu et al 2020), and in accordance with previous observations (Olorundare et al 2001;Jaehyung Cho et al 2005;Mosher 2006b, 2006a;Jaehyung Cho and Mosher 2006). Adhesion signaling through αIIbβ3 is essential to develop full contractility (Figure 4), maximal stress fibers (Lickert et al 2018), as well as a 3D apical anchorage of Fn fibrils as seen in fibroblasts (Figure 1) and a similar mechanomolecular strain within fibrillar adhesions ( Figure 5). We for the first time derive a threshold of ~1 nN per cell-substrate adhesion to activate αIIbβ3 integrins to form 3D fibrils ( Figure 4).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Adhesion signaling of either α6β1 on laminin, α2β1 on Col4, or αIIbβ3 on Fn or fibrin is sufficient to drive αIIbβ3 to assemble Fn fibrils (Figures 1,2,6), in analogy to the pre-activation of α5β1 integrins by αvβ3 in fibroblasts Bharadwaj et al 2017), the initiation of α5β1-containing sliding fibrillar adhesions by α3β1 or α2β1 integrins on Matrigel (Lu et al 2020), and in accordance with previous observations (Olorundare et al 2001;Jaehyung Cho et al 2005;Mosher 2006b, 2006a;Jaehyung Cho and Mosher 2006). Adhesion signaling through αIIbβ3 is essential to develop full contractility (Figure 4), maximal stress fibers (Lickert et al 2018), as well as a 3D apical anchorage of Fn fibrils as seen in fibroblasts (Figure 1) and a similar mechanomolecular strain within fibrillar adhesions ( Figure 5). We for the first time derive a threshold of ~1 nN per cell-substrate adhesion to activate αIIbβ3 integrins to form 3D fibrils ( Figure 4).…”
Section: Discussionsupporting
confidence: 90%
“…As Fn fibrillogenesis is initiated by tensile forces that partially expose cryptic Fn-Fn assembly sites (Hocking, Smith, and McKeown-Longo 1996;Gretchen Baneyx and Vogel 1999) and an impaired cytoskeleton reduces Fn deposition by platelets (J. Cho and Mosher 2006b) and by other cells (G. Baneyx, Baugh, and Vogel 2002), we next analyzed the spatial organization of the actin cytoskeleton using dual color (2C) dSTORM. Confirming previous observations (Lickert et al 2018), we found that the majority of platelets on Fn coatings had formed a highly aligned 'bipolar' filamentous (F-)actin network with pronounced bundles traversing the cell (Figure 1m and Supplementary Figure S1). Longer Fn fibrils emanated parallel to these actin cables at adhesion sites situated at both ends and extended beyond the platelet edge ( Figure 1n).…”
Section: Platelet Fibronectin Fibrils Align With Tensed and Polarizedsupporting
confidence: 91%
See 3 more Smart Citations